The Influence of PKL and Hard Skills on Work Readiness of SMK Students - Azzahra, Nadia; Nurmalasari, Dewi; Maulida, Ervina (RADIANT: Journal of Applied, Social, and Education Studies, 2025)
Vocational High Schools are designed to produce graduates who are ready to enter the workfoce. However, the persistent gap between graduates competencies and industry demands leads to a high unemployment rate, particulary among SMK graduates. This discrepancy suggest that theoretical knowledge alone is insufficient without practical experience and technical competencies. Prior studies have explored various factors influencing work readiness, but limited research has focused specifically on the combined influence of Field Work Practices (PKL) and hard skills in the field of Office Management. This study aims to examine the effect of Field Work Practices and hard skills on the work readiness of 12th-grade students majoring in Office Management at public vocational schools in East Jakarta. The research employed a quantitative approach using a survey method. A total of 123 students from for public vocational schools were selected using proportionate stratified random sampling. Data were collected via questionnaires and analyzed using the Structural Equation (SEM) method with SmartPLS. The results indicate that both Field Work Practices and hard skills have a positive and significant effect on students work readiness. Field Work Practices contribute to work readiness by exposing students to real workplace situations while hard skills ensure the mastery of relevant technical competencies. The findings highlight that work readiness is not solely determined by academic knowledge, but also by the practical experience and skills gained through structured industry exposure and technical training. Thus, schools are encouraged to enhance PKL implementation and hard skill development programs to improve student readiness in facing the challenges of the professional world. Keywords: work readiness, field work practice, hard skill, vocational education, office management